Fostering Landscape Identity Through Participatory Design With Indigenous Cultures of Australia and Aotearoa/New Zealand. Issue 1 (February 2021) - Marques, Bruno; Grabasch, Greg; McIntosh, Jacqueline
To recognize the significance of indigenous cultures and their landscapes as well as to appraise these places, identification and evaluation have to focus on indigenous worldviews rather than on the deeply embedded Western civilization ideals and values of the design. Australian Aboriginal and New Zealand's Maori cultures are genuinely rooted in experiential interrelationships with land with a particular orientation toward relationship and time entrenched in cosmology, narrative, and place. This article explores a participatory design strategy that facilitates and benefits indigenous cultures in Australia and Aotearoa/New Zealand. Using a design-led research approach, this study endeavors to nurture capacity building within "traditional custodians" in order to contribute to the sustainability of rural communities as well as caring for landscape. The article also introduces a framework better suited to nurturing and managing cultural landscapes. This framework demonstrates the potential to simultaneously empower indigenous cultures to protect things that matter but also to enhance their economic, political, and social freedom as they understand it through the lens of their own cultural values.